(untitled) (PerCursos, 2024)
The objective of this paper is to analyze the socialist conception of education present in Nadezhda Krupskaya’s work, situating it within the framework of the Leninist current of Marxism. The pedagogical perspective of the Russian Revolution, in which Krupskaya’s thought is embedded, privileged the awareness of the social totality and was synthesized in the concept of polytechnics, which has particularities when worked through Marxist theory. Based on this assumption, 25 publications by the intellectual and communist leader were examined. For this purpose, the methodology of content analysis was used, and a categorical matrix composed of the following theoretical notions was taken as the basis: polytechnics, labor, system of complexes, women, and democracy. Articulations between these notions were then identified, from which the dimensions of Krupskaya’s socialist education emerge: a) the ideological character of education, labor, and the women’s question; b) the role and nature of the State. Regarding the first aspect, the author highlights the centrality of the women’s question in educational relations. As for the second, we conclude that her conception is directly influenced by the Leninist debate on the State.